Transient Postural Vestibulo-Cerebellar Syndrome in Three Dogs With Presumed Cerebellar Hypoplasia - Prikryl, Miroslav; Caine, Abby; Palus, Viktor (Frontiers in Veterinary Science, 2020)
This case study presents a unique transient postural vestibular syndrome in three dogs. The transient postural symptoms present as pronounced vestibulo-cerebellar signs after altering the position of the head. Magnetic resonance imaging findings of the brain suggest caudal cerebellar hypoplasia, affecting vermis and floccular lobes bilaterally in case 1, and hypoplasia of the nodulus vermis in cases 2 and 3. No progression of clinical signs was reported in minimum of four months period.